Effects of Inclusive Leadership on Employee Voice Behavior and Team Performance: The Mediating Role of Caring Ethical Climate - Qi, Lei; Liu, Bing (Frontiers in Communication, 2017)
As an emerging research field of leadership, inclusive leadership reflects the new style of leadership demanded by researchers and practitioners. Is it a leadership style that can better integrate employees and organizations, and adapt to new complex management situation? Based on theories of social exchange, organizational support, and self-determination, this study investigated the impact of inclusive leadership on employee voice behavior and team performance through caring ethical climate. We evaluated the model with a time-lagged data of 329 team members from 105 teams in six cities in China. Results indicated as following: inclusive leadership was positively correlated with employee voice behavior at the individual level and team performance at the team level; caring ethical climate mediated the relationship between inclusive leadership and employee voice behavior at the individual level, as well as mediated the relationship between inclusive leadership and team performance at the team level. This study revealed the mechanism of the positive cross-level effects of inclusive leadership on the caring ethical climate, employee voice behavior, and team performance. These findings also provided important contributions for human resource management and practice.